1966
DOI: 10.1037/h0023820
|View full text |Cite
|
Sign up to set email alerts
|

Fantasy need achievement as a motivational construct.

Abstract: The McClelland-Atkinson theory that arousal of achievement fantasy depends upon arousal of the achievement motive is examined critically in light of accrued empirical evidence. The effects of achievement-arousal conditions on fantasy n Ach are shown to be probably nonmotivational. n Ach scores are shown to be correlated with performance measures in about \ of the studies reported, but the pattern of hypothesis confirmation presents the theory with difficulties. The addition of perceptual and cognitive situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 71 publications
(38 reference statements)
3
52
0
Order By: Relevance
“…There are lots of reasons: People keep insisting that the n Achievement score is invalid because it will not predict grades in school-which is ironic since it was designed precisely to predict life outcomes and not grades in school. Or they argue it does not predict all types of achievement (Klinger, 1966)-when, of course, it is not supposed to, on theoretical grounds. But the practical problem (outside the tedium of content coding) is the unreliability of operant thought measures.…”
Section: Tests Should Be Designed To Reflect Changes In What the Indimentioning
confidence: 99%
“…There are lots of reasons: People keep insisting that the n Achievement score is invalid because it will not predict grades in school-which is ironic since it was designed precisely to predict life outcomes and not grades in school. Or they argue it does not predict all types of achievement (Klinger, 1966)-when, of course, it is not supposed to, on theoretical grounds. But the practical problem (outside the tedium of content coding) is the unreliability of operant thought measures.…”
Section: Tests Should Be Designed To Reflect Changes In What the Indimentioning
confidence: 99%
“…Klinger (1966) concluded that correlations between TAT measures and performance outcomes were significant only in 50% of the studies. Fineman (1977) reviewed studies in which more than one measure of nAch was involved (TAT, questionnaires, other projective techniques) and found no evidence for convergent validity.…”
Section: Validitymentioning
confidence: 99%
“…Atkinson and Iitwin (1956), for example, failed to find any evidence that male college students for whom Mgf'•Ms avoided moderately difficult tasks in preference for low or high difficult tasks. Following a rather extensive review of achievement motivation literature, Klinger (1966) argued that only about half of the relevant published studies cited significant relationships between measure of need achievement and performance in a manner supportive of the theory. He also contended that postdictive rather than predictive relationships are often discussed and defended and that "the pattern of hypothesis confirmation presents the theory with difficulties" (p. (P-291).…”
Section: Achievement Motivation Theorymentioning
confidence: 97%